The Title Hierarchy of the Last Komnenoi and the Angelos Dynasty – from Sebastohypertatos to Sebastokrator - Lachowicz, Paweł (Studia Ceranea, 2021)
The system of dignities introduced by Alexios I Komnenos was an answer for the need of a new reformed title hierarchy, adequate for aristocratic model of exercising power. It served as a clear manifestation of the special privileged position of emperor’s kinsmen. The titles granted to those relatives and affines can be traced accurately up to the reign of Manuel I. So far, however, little space has been devoted to the analysis of that system during the Angelos dynasty. It is often generally assumed following Niketas Choniates testimony, that the title hierarchy in the late 12th century suffered certain loss of value or inflation. It is worth taking a closer look at this process, on the example of the titles traditionally granted to the closest family members, at the courts of Andronicus I Komnenos and the Angeloi. I would like to focus particularly on those dignities, that at the time of the Komnenoi were given to the emperor’s siblings and his sons-in-law – from sebastohypertatos to sebastokrator. That part of the title hierarchy was much closer to a ruler, making it easier to trace. The basic problem encountered by researchers of this period is the small number of sources, not allowing for full reconstruction of the title hierarchy. However, very limited information found in the written sources can be complemented by aristocratic lead seals, which often included the dignity of their owners. From such an analysis emerges a picture of a steady evolution of the Komnenian system. The emperors of the late 12th century adjusted court dignities to need at hand. Yet that process doesn’t seem to diminish significantly the value of the highest titles.